Methods and Tastes in Modern Continuum Mechanics 2011
DOI: 10.1007/978-94-007-1884-5_19
|View full text |Cite
|
Sign up to set email alerts
|

A Large Strain Isotropic Elasticity Model Based on Molecular Dynamics Simulations of a Metallic Glass

Abstract: For an isotropic hyperelastic material, the free energy per unit reference volume, ψ, may be expressed in terms of an isotropic function ψ =ψ(E) of the logarithmic elastic strain E = ln V. We have conducted numerical experiments using molecular dynamics simulations of a metallic glass to develop the following simple specialized form of the free energy for circumstances in which one might encounter a large volumetric strain tr E, but the shear strain √ 2|E 0 | (with E 0 the deviatoric part of E) is small but no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…For these reasons the quadratic Hencky model is used in theoretical investigations and in physical applications [149,8,39,40,77,192,86,88,87,83]. We observe also a renewed interest in this class of isotropic slightly compressible hyperelastic solids originally proposed by Hencky [100,102,101,103,98]. The strain energy W H is also often used in commercial FEM-codes.…”
Section: Scope Of Investigationmentioning
confidence: 99%
See 2 more Smart Citations
“…For these reasons the quadratic Hencky model is used in theoretical investigations and in physical applications [149,8,39,40,77,192,86,88,87,83]. We observe also a renewed interest in this class of isotropic slightly compressible hyperelastic solids originally proposed by Hencky [100,102,101,103,98]. The strain energy W H is also often used in commercial FEM-codes.…”
Section: Scope Of Investigationmentioning
confidence: 99%
“…This decomposition problem was studied later in the papers [7,114]. Gearing and Anand [89] (see also [98,68]) recently proposed an energy of the form 17…”
Section: Previous Work In the Spirit Of Our Investigationmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the fracture energy (toughness) of Fe-based BMG alloys was correlated with changes in the G/K ratio as well as the Poisson's ratio by Lewandowski et al 205 Through a broad survey of the literature, it was shown 209,210 model also predicts the importance of elastic constant ratio on the toughness of metallic glasses. 211 The ductility of conventional crystalline metals has been shown to increase by the introduction of thin metallic glassy ribbons into them. 212 Therefore, researchers have utilised this concept to increase the ductility of BMG alloys and have achieved some amount of success.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…In the first part [36] we have summarized the well-known unique features of the quadratic Hencky strain energy W H based exclusively on the natural strain tensor log U . The Hencky model is definitely one of the most widely used strain energies in the small elastic strain regime [21,23,22,24,8,9,20]. In [36], however, we also pointed out that the quadratic Hencky energy has some serious shortcomings.…”
Section: Motivationmentioning
confidence: 91%